2020
DOI: 10.1016/j.jvs.2019.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of artery and vein diameters on autogenous arteriovenous access patency

Abstract: Objective: Previous investigations have suggested that a minimum venous outflow diameter (MVOD) and perianastomotic arterial diameter are associated with successful autogenous arteriovenous maturation and patency. The goal of this study was to determine anatomic and clinical variables that may influence access patency to guide optimal autogenous access configuration selection. Methods: Accesses created from 2010 to 2016 were analyzed from data entered into a prospective database. Preprocedure duplex ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
1
33
2
Order By: Relevance
“…3 A relationship between AVF maturation and vein diameter has been reported, but arterial diameter has not been extensively studied for its effect on maturation. 8,[16][17][18] Our results did not show vein diameter to be a significant factor for AVF maturation. Kakkos meta-analysis that the one-stage technique was associated with a higher failure to mature, which was not observed in previous retrospective studies.…”
Section: Discussioncontrasting
confidence: 63%
“…3 A relationship between AVF maturation and vein diameter has been reported, but arterial diameter has not been extensively studied for its effect on maturation. 8,[16][17][18] Our results did not show vein diameter to be a significant factor for AVF maturation. Kakkos meta-analysis that the one-stage technique was associated with a higher failure to mature, which was not observed in previous retrospective studies.…”
Section: Discussioncontrasting
confidence: 63%
“…Stoumpos et al 16 from the United Kingdom in a large and contemporary study concluded that surgical AVF success rates have not improved over time, with only 55.3% of AVFs being used at the end of a mean 11.8month period and a primary failure rate of 29%. Clearly, this problem calls for solutions, and although vessel status and diameter, patient comorbidities, use of locally applied drugs, and technical or anesthesiology considerations have been implicated or tested with variable results, [17][18][19][20][21][22] none have established a dramatic answer. All these variables have been shown to have some predictive value or promise toward establishing prolonged functional patency, but creating a reliable and durable autogenous access that is successfully replicated in most centers remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This study also investigated the effect of vascular (arterial and venous) diameters on AVF primary dysfunction. Even though Misskey Jonathan and hamidzadeh Ramin (24) found radial arterial diameter (<2.1mm) to be an independent risk factors for AVF dysfunction. However, we report dissimilar findings: Vascular diameter not to be an risk factor for AVF dysfunction, probably due to strong emphasis on vascular diameter before surgery in our center.…”
Section: Discussionmentioning
confidence: 99%